Effects of payment for ecosystem services and agricultural subsidy programs on rural household land use decisions in China: Synergy or trade-off?. (February 2019) - Wang, Ying; Bilsborrow, Richard E.; Zhang, Qi; Li, Jiangfeng; Song, Conghe
Abstract: While agri-environmental policies that target different problems are often simultaneously implemented at the same place, little attention has been paid to the interactions of the policies, either in policy design or evaluation. The goal of this study is to understand the potential interactions (synergies or trade-offs) between an agricultural subsidy program and two payments for ecosystem services (PES) programs, namely the Conversion of Cropland to Forest Program (CCFP) and the Ecological Welfare Forest Program (EWFP), and their effects on household land use decisions. Data collected from 481 rural households in Anhui, China are used for the exploration. The Sustainable Livelihoods Framework is used to identify factors that may affect household land use decisions, i.e., whether to expand, stabilize, or shrink the cropland area, and further to identify whether to abandon or rent out land if the shrinkage decision is made. The results show that: (1) most rural households (58%) in the study area reduce cultivated land, and mostly via cropland abandonment, while only 16% of the interviewed households expand land area; (2) the most important factors determining cropland expansion include farm tools and transportation equipment, while the number of parcels and financial support are the dominant factors that stimulate households to adopt abandoning over renting-out decisions when deciding to shrink cropland; (3) EWFP payment has a significant direct impact on cropland management, while no significant influences are observed from the other two programs; (4) there exist complex trade-offs among the three government programs with similar or conflicting aims, which highlights the need to take policy interactions into account when designing new agri-environmental policies.